A practical guide to world philosophies : selves, worlds, and ways of knowing - Kirloskar-Steinbach, Monika; Kalmanson, Leah, 1977- (London, England : Zed Books, 2021)
Traditions throughout the world and across history have tackled fundamental questions about the human condition. This one-of-a-kind guide shows how these different philosophies can be effectively studied together. Monika Kirloskar-Steinbach's and Leah Kalmanson's introduction marks a break from conventional approaches. Instead of assuming philosophy has always operated with a single, easily identifiable conceptual framework across space and time, which we call-and have always called-philosophy, they attest to the plurality of concepts and methods adopted at different times and places. The book serves as a practical teaching guide to the theoretical and methodological diversification of philosophy as practiced in academia today. Complementing the Bloomsbury Introductions to World Philosophies series, it covers a variety of traditions featured in the book series, exploring how Anglo-American, Chinese, Indian, African, Islamicate, and Maori thinkers have all addressed fundamental questions such as: How do we understand ourselves and our relations to others? How do we understand our world? How do we seek knowledge, share knowledge, and, importantly, intervene in the norms of received knowledge when needed? Featuring teaching notes, discussion questions, and a list of further reading, this is a book packed with the background, guidance, and tools required to teach different philosophies. Through it we come to see why making room for different conceptual frameworks improves our understanding of ourselves and the worlds we live in. -- Provided by publisher.
"Offering a teaching guide for instructors looking to broaden their view of philosophy, diversify their teaching, or discover a new way of thinking about our place in the world, this book explores how Anglo-American, Chinese, Indian, African, Islamic, and Maori thinkers have all addressed fundamental questions in philosophy. Featuring teaching notes, discussion questions, and a list of further reading, this is a book packed with the background, guidance, and tools required to teach different philosophies"--
Why World Philosophies? : Standard Comparisons and Global Concerns -- World Philosophies and Global Concerns -- Conclusion: Moving Forward -- Brief Chapter Overview -- World Philosophies in Historical Perspective: Racism and Development of Academic Philosophy in the Eighteenth Century -- Racism and Philosophy Today -- Philosophy in Translation -- Conclusion: Moving Forward -- Relational Knowing, Self-Making and the Study of World Philosophies: Why a Relational Knower? -- What is a Relational Knower? -- Power Dynamics in Relational Knowing -- Potential of Relational Knowing in Studying World Philosophies -- Conclusion: Moving Forward -- Knowing the World, World-Making and the Study of World Philosophies: Knowing the World Relationally -- African Personhood and Knowing -- Knowing and Labelling the World of Philosophies -- Conclusion: Moving Forward -- Knowing Relationally and Making Knowledge: Presentist Concerns and Knowledge Making -- Inheritance and Representation, or Actors and Scholars -- The Making of Islamic Philosophy -- The Making of Indian Philosophy -- Summary of the Book: Study Guide Material
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Philosophy -- Introductions; Philosophy -- History; Non-Western philosophy; Electronic books